2015
DOI: 10.1007/s11356-015-4539-y
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for controlling air pollutants and their environmental impacts generated from coal-based electricity generation in China

Abstract: This study aims at qualifying air pollutants and environmental impacts generated from coal-based power plants and providing useful information for decision makers on the management of coal-based power plants in China. Results showed that approximately 9.03, 54.95, 62.08, and 12.12% of the national carbon dioxide, sulfur dioxide, nitrogen oxides, and particulate matter emissions, respectively, in 2011were generated from coal-based electricity generation. The air pollutants were mainly generated from east China … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 19 publications
2
5
0
1
Order By: Relevance
“…As some tech companies have started using solar and wind for power generation, other sectors will also follow this campaign to reduce their carbon footprint. This result validates the previous studies conducted for China (Akadiri et al, 2020;Munir & Riaz, 2020;Xu et al, 2015;Zhang, 2019); Spain (Zarco-Soto et al, 2020); South Asian economies (Munir & Riaz, 2019); Bangladesh (Shahbaz et al, 2014); ASEAN countries (Lean & Smyth, 2010); Pakistan (Rehman et al, 2019) and BRICS (Haseeb et al, 2019).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As some tech companies have started using solar and wind for power generation, other sectors will also follow this campaign to reduce their carbon footprint. This result validates the previous studies conducted for China (Akadiri et al, 2020;Munir & Riaz, 2020;Xu et al, 2015;Zhang, 2019); Spain (Zarco-Soto et al, 2020); South Asian economies (Munir & Riaz, 2019); Bangladesh (Shahbaz et al, 2014); ASEAN countries (Lean & Smyth, 2010); Pakistan (Rehman et al, 2019) and BRICS (Haseeb et al, 2019).…”
Section: Resultssupporting
confidence: 91%
“…Yorucu and Varoglu (2020) studied the nexus among industrial production, electricity consumption, economic growth, and CO 2 e in selected small island states. Based on the FMOLS and DOLS estimations, the authors found that a one percent increase in electricity consumption predicted an upsurge of 0.79 percent in CO 2 e. In the same way, others studies have also reported a positive connection between electricity consumption and CO 2 e for China (Akadiri et al, 2020;Munir & Riaz, 2020;Ou, Xiaoyu, & Zhang, 2011;Xu, Hong, Ren, Wang, & Yuan, 2015;Zhang, 2019); Spain (Zarco-Soto, Zarco-Periñán, & Sánchez-Durán, 2020); South Asian economies (Munir & Riaz, 2019); Bangladesh (Shahbaz, Salah Uddin, Ur Rehman, & Imran, 2014); ASEAN countries (Lean & Smyth, 2010); Pakistan (Rehman et al, 2019) BRICS (Cowan, Chang, Inglesi-Lotz, & Gupta, 2014;Haseeb, Xia, Saud, Ahmad, & Khurshid, 2019); and Kuwait (Salahuddin, Alam, Ozturk, & Sohag, 2018).…”
Section: The Relationship Between Electricity Consumption and Co 2 Ementioning
confidence: 85%
“…As some tech companies have started using solar and wind for power generation, other sectors will also follow this campaign to reduce their carbon footprint. This result validates the previous studies conducted for China (Akadiri et al 2020 ; Munir and Riaz 2020 ; Xu et al 2015 ; Zhang 2019 ); Spain (Zarco-Soto et al 2020 ); South Asian economies (Munir and Riaz 2019 ); Bangladesh (Shahbaz et al 2014 ); ASEAN countries (Lean and Smyth 2010 ); Pakistan (Rehman et al 2019 ); and BRICS (Haseeb et al 2019 ).…”
Section: Resultssupporting
confidence: 87%
“…Yorucu and Varoglu ( 2020 ) studied the nexus among industrial production, electricity consumption, economic growth, and CO 2 e in selected small island states. Based on the FMOLS and DOLS estimations, the authors found that a 1% increase in electricity consumption predicted an upsurge of 0.79% in CO 2 e. In the same way, other studies have also reported a positive connection between electricity consumption and CO 2 e for China (Akadiri et al 2020 ; Munir and Riaz 2020 ; Ou et al 2011 ; Xu et al 2015 ; Zhang 2019 ); Spain (Zarco-Soto et al 2020 ); South Asian economies (Munir and Riaz 2019 ); Bangladesh (Shahbaz et al 2014 ); ASEAN countries (Lean and Smyth 2010 ); Pakistan (Rehman et al 2019 ) BRICS (Cowan et al 2014 ; Haseeb et al 2019 ); and Kuwait (Salahuddin et al 2018 ). Table 4 depicts the summary of the selected studies on the nexus between electricity consumption and CO 2 e.…”
Section: Literature Reviewmentioning
confidence: 84%
“…Most of the NO x are mainly produced by human activities, including stationary source (coal) combustion 8 , 9 and mobile source (motor vehicle) combustion. 10 In recent years, due to the popularization of high-efficiency three-way catalysts and denitration devices in coal-fired power plants, NO x has been controlled to a certain extent. 11 However, in industries such as steel, coking, cement, glass, and ceramics, 12 16 NO x pollution is still serious.…”
Section: Introductionmentioning
confidence: 99%